(untitled) (International Journal of Engineering and Computer Science, 2013)
Large quantity of bagasse is produced annually and not much use is made of them except as waste. This investigation was carried out in an effort to search for raw materials to replace the presently imported long fibre pulp in Nigeria. Bagasse was macerated and the properties of its pulp were evaluated. Sample sheets of paper were produced using hand sheet method and were duly tested for tearing resistance, tensile strength and burst strength. The pulp has fairly long fibre length of 2.071mm. Its papers posses high tearing resistance of 1226.25mN and tear factor 125.00m2 but low tensile strength of 6.50Nm/g and burst strength of 57.5kPa. Therefore its paper products can be used for writing and printing applications